2022
DOI: 10.3390/ijms23137130
|View full text |Cite
|
Sign up to set email alerts
|

Cucurbitacin B Down-Regulates TNF Receptor 1 Expression and Inhibits the TNF-α-Dependent Nuclear Factor κB Signaling Pathway in Human Lung Adenocarcinoma A549 Cells

Abstract: Pro-inflammatory cytokines, such as tumor necrosis factor-α (TNF-α), induce the expression of intracellular adhesion molecule-1 (ICAM-1) by activating the nuclear factor κB (NF-κB) signaling pathway. In the present study, we found that cucurbitacin B decreased the expression of ICAM-1 in human lung adenocarcinoma A549 cells stimulated with TNF-α or interleukin-1α. We further investigated the mechanisms by which cucurbitacin B down-regulates TNF-α-induced ICAM-1 expression. Cucurbitacin B inhibited the nuclear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 63 publications
1
5
0
Order By: Relevance
“…Quantitative results obtained through flow cytometry revealed consistent conclusions (Figure a). The improved affinity of Neutrosome­(L) to tumor cells might be attributed to the interaction of LFA-1 enriched on Neutrosome­(L) with ICAM-1 on the A549 cell membrane, which mediated the promotion of cellular internalization. , Later on, the tumor penetration ability was investigated on the tumor spheroid in vitro. A tumor spheroid treated with DiD-labeled liposome displayed the lowest fluorescence intensity and presented very weak fluorescence at a depth of 40 μm.…”
Section: Resultsmentioning
confidence: 99%
“…Quantitative results obtained through flow cytometry revealed consistent conclusions (Figure a). The improved affinity of Neutrosome­(L) to tumor cells might be attributed to the interaction of LFA-1 enriched on Neutrosome­(L) with ICAM-1 on the A549 cell membrane, which mediated the promotion of cellular internalization. , Later on, the tumor penetration ability was investigated on the tumor spheroid in vitro. A tumor spheroid treated with DiD-labeled liposome displayed the lowest fluorescence intensity and presented very weak fluorescence at a depth of 40 μm.…”
Section: Resultsmentioning
confidence: 99%
“…[ 54 ] TNF‐α further activates NF‐κB, a transcription factor that ultimately induces transcriptional activation of genes related to oxidative stress and inflammation. [ 55 ] TNFR1 is widely expressed in most cell lines and is considered a key mediator of TNF‐α signaling, which is primarily responsible for promoting inflammation and inducing apoptosis. [ 56 ] In response to ligand binding, the TNFR1 complex activates IκB kinase, which phosphorylates the IκB protein, leading to its dissociation from the NF‐κB trimer.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Liu et al found that CuB suppressed the growth and invasion of gefitinib-resistant NSCLC cells by inducing lysosomal EGFR degradation and by downregulating the CIP2A/PP2A/Akt signaling axis [ 135 ]. Kusagawa et al reported that CuB also downregulated TNF-R1 at the initial stage of the TNF-α-dependent NF-κB signaling pathway [ 136 ], while Shukla et al anticipated that CuB inhibited the metastasis of non-small-cell lung cancer (NSCLC) through suppression of the Wnt/β-catenin signaling axis [ 137 ]. Based on these findings, it is clear that CuB has the potential to be a powerful agent in the treatment of cancer.…”
Section: Detailed Results and Discussionmentioning
confidence: 99%